1994
DOI: 10.1056/nejm199401273300403
|View full text |Cite
|
Sign up to set email alerts
|

Results of Conservative Management of Clinically Localized Prostate Cancer

Abstract: The strategy of initial conservative management and delayed hormone therapy is a reasonable choice for some men with grade 1 or 2 clinically localized prostate cancer, particularly for those who have an average life expectancy of 10 years or less. New treatment strategies are needed for men with grade 3 prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
336
3
28

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 855 publications
(384 citation statements)
references
References 26 publications
12
336
3
28
Order By: Relevance
“…As reported in the literature, expectant management of prostate cancer may be debatable in younger patients. 7,19 Data are lacking in this study to differentiate stages T 1a and T 1b in the group of patients under surveillance or treated by TURP alone. A multivariate analysis on the influence of non-medical determinants such as geographical region and sector of activity (public and private) on the different treatment choices will be provided in a subsequent publication.…”
Section: Discussionmentioning
confidence: 97%
“…As reported in the literature, expectant management of prostate cancer may be debatable in younger patients. 7,19 Data are lacking in this study to differentiate stages T 1a and T 1b in the group of patients under surveillance or treated by TURP alone. A multivariate analysis on the influence of non-medical determinants such as geographical region and sector of activity (public and private) on the different treatment choices will be provided in a subsequent publication.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3] For example, Albertsen et al reported the long-term outcome of watchful waiting for 767 men diagnosed with clinically localised prostate cancer between 1971 and 1984, aged from 55 to 74 y, who were identified from the Connecticut Tumor Registry. The 15-year prostate cancer mortality for men with Gleason 6 disease was 18-30%, while their 15-y risk of death from other causes was 25-59%.…”
Section: The Natural History Of Early Prostate Cancermentioning
confidence: 99%
“…18 These six series originate from four different countries, Sweden, Israel, United Kingdom and the United States. Altogether, data from 828 patients were available and 820 patients were evaluable both with respect to tumor grade and tumor stage.…”
Section: Pooled Analysis Of Series On Deferred Treatmentmentioning
confidence: 99%
“…One example of this is the aforementioned pooled analysis where patients from four different countries were included. 18 Today it is more or less accepted, even by the most aggressive surgeons, that patients with lowgrade low-stage prostate cancer with a life expectancy of 10±15 y or less may not bene®t from aggressive treatment but could be offered deferred treatment as an alternative. 30 This acceptance of deferred treatment is based on the understanding that in most studies the disease-speci®c survival is between 85 and 90% at 10 y after the diagnosis and this does not seem to differ greatly from other treatments up to that point of time.…”
Section: Commentsmentioning
confidence: 99%